1994
DOI: 10.1148/radiographics.14.5.7991816
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the process of quantitative ultrasonic tissue characterization.

Abstract: Because the human vision system cannot distinguish the broad range of gray values that a computer visual system can, computerized image analysis may be used to obtain quantitative information from ultrasonographic (US) real-time B-mode scans. Most quantitative US involves programming an off-line comput-I Ironi the 1)cpartrnents of Radiology. Arkansas Childrens hospital and tniversity of Arkansas for Medical Sciences, Little Rock (J.W.A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 17 publications
1
17
0
1
Order By: Relevance
“…Visual inspection of US images is limited by the ability of the human eye to detect subtle changes in tissue echogenicity, which can lead to underestimation of mild white matter lesions. One of the methods used to quantitatively measure sonographic data is textural feature analysis; this approach has been useful for identifying diffuse diseases of the liver (Allison et al 1994;Sun et al 1996). Several authors (Barr et al 1996;Simaeys et al 2000;Vansteenkiste et al 2005;Hope et al 2008) have attempted to reliably quantify neonatal brain lesions; however, a practical method for routine use in clinical practice remains to be established.…”
Section: Introduction and Literaturementioning
confidence: 99%
“…Visual inspection of US images is limited by the ability of the human eye to detect subtle changes in tissue echogenicity, which can lead to underestimation of mild white matter lesions. One of the methods used to quantitatively measure sonographic data is textural feature analysis; this approach has been useful for identifying diffuse diseases of the liver (Allison et al 1994;Sun et al 1996). Several authors (Barr et al 1996;Simaeys et al 2000;Vansteenkiste et al 2005;Hope et al 2008) have attempted to reliably quantify neonatal brain lesions; however, a practical method for routine use in clinical practice remains to be established.…”
Section: Introduction and Literaturementioning
confidence: 99%
“…Conventional B-mode ultrasound images are formed by transmitting an acoustic pulse into the body, followed by receipt, processing and display of the amplitude of returning echo signals. Unfortunately, not all of this information is detectable with the human eye on hard copy or in real-time B-mode image [18]. This drawback has prompted investigations to search for other ways to process echo signals and obtain quantitative ultrasonographic data from tissues [19].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that these measurable acoustic properties depend on cell size, the material between cells and the ultrastructure [18]. The texture analysis was used in a number of anatomical sites in the human body, including precision of breast pathologies and hepatic steatosis [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…1). These parameters were defined GÜLTİKEN, KANCA, GÜNEN, KUTSAL, EMRE, EVANGELOS, ASLAN by Allison et al [26] and Moss et al [27] as: Mean Gray Level (Arithmetical average grey level of all pixels in picture, defines the brightness), Mean Gradient (Variations in grey values of neighbor pixels, defines microtexture of sample), Homogeneity (Uniformity of grey value combination of neighbor pixels in defined matrix, defines either micro-or macrotexture of sample), Entropy (A measure of the uniformity of matrix values), Contrast (A measure of how many large grey-level differences are present in the ROI), Gray Value (The brightness of pixels in a digitized image).…”
Section: Animal Grouping and Image Acquisitionmentioning
confidence: 99%